STRATEGI KOMUNIKASI DINAS PARIWISATA DALAM MENINGKATKAN PARTISIPASI MASYARAKAT MEMBANGUN WISATA AIR TERJUN GUMBU PARK DI NIAS SELATAN - Esta Ningsih Harita; Elok Perwirawati (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Darma Agung, 2021)
This study aims at determining the extent of the communication strategy carried out by the South Nias Regency Tourism Office, and the participation of the people of Hilisataro Nandrisa Village in the development of the Gumbu Park Waterfall tourist attraction. This is considering the development of the tourist attraction has not been able to run. Although crowded with visitors, the available facilities cannot be said to be feasible at all. Previously, Gumbu Park Waterfall was listed in the Master Plan for Tourism Development by the South Nias Regency Government. There is also a research methodology that is used qualitatively, to describe descriptively the social phenomena that are explored and clarified. Selection of informants using non-probability sampling method by providing opportunities for members of the population to be selected as samples based on certain criteria, consisting of key, main and supporting informants, as many as 5 (five) people. Several field findings have answered the obstacles to the construction of Gumbu Park Waterfall, including: unclear land ownership status; no budget allocation from the village government of Hilisataro Nandrisa; and ineffective communication strategies. In conclusion, the communication strategy carried out by the Tourism Office of South Nias Regency as a whole cannot be said to be quite effective. In addition, the participation of the people of Hilisataro Nandrisa Village in the construction of the Gumbu Park Waterfall tourist attraction is still small.